RBMX family proteins connect the fields of nuclear RNA processing, disease and sex chromosome biology. (March 2019) - Elliott, David J.; Dalgliesh, Caroline; Hysenaj, Gerald; Ehrmann, Ingrid
Abstract: RBMX is a ubiquitously expressed nuclear RNA binding protein that is encoded by a gene on the X chromosome. RBMX belongs to a small protein family with additional members encoded by paralogs on the mammalian Y chromosome and other chromosomes. These RNA binding proteins are important for normal development, and also implicated in cancer and viral infection. At the molecular level RBMX family proteins contribute to splicing control, transcription and genome integrity. Establishing what endogenous genes and pathways are controlled by RBMX and its paralogs will have important implications for understanding chromosome biology, DNA repair and mammalian development. Here we review what is known about this family of RNA binding proteins, and identify important current questions about their functions.